Thrombolysis in Pulmonary Embolism: Octagenarians Deserve More Attention! - Yoo, Hugo Hyung Bok [UNESP] (2022)
Universidade Estadual Paulista Júlio de Mesquita Filho Faculdade de Medicina Campus de Botucatu-Clínica Médica, SP